Dukungan keluarga dalam mencegah postpartum blues pada ibu primipara: A literature review - Sulistiani, Sulistiani; Erika, Erika; Wahyuni, Sri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Postpartum blues is a mild psychological disorder commonly experienced by mothers after childbirth, especially primiparous mothers who have no prior experience dealing with physical and emotional changes after delivery. This condition is characterized by symptoms such as mood swings, anxiety, frequent crying, and emotional fatigue. One important protective factor in preventing postpartum blues is family support. Purpose: To systematically review family support in preventing postpartum blues among primiparous mothers. Method: A literature review was conducted by searching for relevant scientific articles from databases such as Google Scholar, PubMed, ScienceDirect, Semantic Scholar, ResearchGate, and BMC. The analyzed articles were published between 2020 and 2024. Results: The analysis shows that family support, especially from husbands, has a significant relationship in preventing and reducing the risk of postpartum blues. Emotional support, practical assistance, open communication, and active involvement in infant care are key elements in supporting maternal mental health. Qualitative studies also indicate that family support provides a sense of being valued and strengthens mothers’ ability to cope with postpartum changes. Conclusion: Family support has been proven to play an important role as an effective non-medical intervention in preventing postpartum blues among primiparous mothers. Keywords: Family Support; Postpartum Blues; Primiparous Mothers. Pendahuluan: Postpartum blues merupakan gangguan psikologis ringan yang umum dialami oleh ibu setelah melahirkan, terutama pada ibu primipara yang belum memiliki pengalaman menghadapi perubahan fisik dan emosional pascapersalinan. Kondisi ini ditandai oleh gejala seperti perubahan suasana hati, kecemasan, mudah menangis, dan kelelahan emosional. Salah satu faktor protektif yang penting dalam mencegah terjadinya postpartum blues adalah dukungan dari keluarga. Tujuan: Untuk mengkaji secara sistematis dukungan keluarga dalam mencegah postpartum blues pada ibu primipara. Metode: Literature review dengan menelusuri artikel ilmiah yang relevan dari database Google Scholar, PubMed, ScienceDirect, Semantic Scholar, ResearchGate, dan BMC. Artikel yang dianalisis dipublikasikan dalam rentang tahun 2020 hingga 2024. Hasil: Analisis menunjukkan bahwa dukungan keluarga, terutama dukungan dari suami, memiliki hubungan yang signifikan dalam mencegah dan menurunkan risiko postpartum blues. Dukungan emosional, bantuan praktis, komunikasi terbuka, dan keterlibatan aktif dalam pengasuhan bayi menjadi elemen utama dalam mendukung kesehatan mental ibu. Studi kualitatif juga menggambarkan bahwa dukungan keluarga memberikan rasa dihargai dan memperkuat kemampuan ibu dalam menghadapi perubahan pascapersalinan Simpulan: Dukungan keluarga terbukti berperan penting sebagai intervensi non-medis yang efektif dalam mencegah postpartum blues pada ibu primipara. Kata Kunci: Dukungan Keluarga; Ibu Primipara; Postpartum Blues.